Globalizing Modeling Languages. - Combemale, Benoit; DeAntoni, Julien; Baudry, Benoit; France, Robert B.; Jezequel, Jean-Marc; Gray, Jeff (Computer (00189162), 2014)
Coordinating domain-specific modeling languages provides support for language heterogeneity in software-intensive systems' development and runtime management.